The validation of the analytical method (HPLC), use for identification and assay of the pharmaceutical active ingredient, colistine sulphate and the finished product Colidem 50 – hydrosoluble powder, in SC DELOS impex ‘96 SRL - Maria Neagu,; Cristina Marinescu,; Carmen Popescu (Medicamentul Veterinar, 2011)
In SC DELOS IMPEX ’96 SRL the quality of the active pharmaceutical ingredient (API) for the finished product Colidem 50 - hydrosoluble powder is make according to European Pharmacopoeia, curent edition. The method for analysis use in this purpose is the compendial method „Colistine sulphate” in E.P. in current edition and represent a optimized variant, developed and validated „in house”.The parameters which was included in the methodology validation for chromatographic method are the follow: Selectivity/Specificity, Linearity, Range of Linearity, Limit of Detection and Limit of Quantification, Precision (Repeatability - intra day, inter-Day Reproducibility), Accuracy, Robustness, Stability Solutions and System Suitability.